TRACES OF JOHNSON IN THE LANGUAGE OF FANNY BURNEY - Bax, Randy (International Journal of English Studies, 2009)
It has often been claimed that Frances Burney (1752-1840) was influenced linguistically by Samuel Johnson (1709-1784). Sorensen (1969: 390), and others with him, have even called her a "slavish imitator" of the language which Johnson used in his Rambler essays. Although far from simple guesswork, quantitative studies such as Sorensen's remain impressionistic, which makes it difficult to incorporate his (and similar) observations in quantitative socio-histoncal linguistic studies of the English language. In the present study, the question whether Burney was indeed a serious imitator of Johnson's usage is answered by looking at the problem from a quantitative rather than qualitative perspective, and addressed within the framework of histoncai social network analysis.